Produção de fator de necrose tumoral (TNF) em hemoculturas humanas induzida por agonistas de TLR2 (toll-like receptor 2): modulação pelo fator ativador de plaquetas (PAF) - Galdino Júnior, Hélio (2008)
Microorganisms express conserved molecules which ones activate the innate immune system. These molecules are known as pathogen-associated molecular patterns (PAMPs), such as lipopolysaccharide (LPS) and bacterial lipoproteins. The PAMPs can be recognized by Toll-like receptors (TLR). The innate immunity activation through TLR pathway induces pro-inflammatory cytokines and lipid mediators, as tumor necrosis factor (TNF) and platelet-activating factor (PAF), respectively. Several reports showed the interaction between TLR4 and PAF receptor (PAFR) signaling to the TNF production; however, the interaction between PAF and other TLR was poorly investigated. The aim of this study was to evaluate the PAF regulatory activity on TLR2-induced TNF production. Thus, Mycoplasma fermentans PG 18 lipoproteins (LAMPf), TLR2/TLR6 agonists and Pam3Cys, a synthetic lipopeptide agonist of TLR2/TLR1 were added to human whole blood cultures and TNF was evaluated by enzyme-linked immunosorbent assay. To evaluate the effects of endogenous PAF on TNF production, a PAF receptor antagonist, WEB2170 was used, and to evaluate the effect of exogenous PAF, PAF was added to the cultures. The blood cultures were also activated with Gram-positive or negative heat-killed bacteria (Staphylococcus aureus or Escherichia coli). The TLR2 expression on polymorphonuclear (PMN) and monocytes were evaluated by flow cytometry, analyzing total cellularity for PMN and CD14+ cells for monocytes. LAMPf, Pam3Cys or LPS induced TNF and the treatment with WEB2170 increased TNF production after TLR2 activation, but not after TLR4 activation. Priming of the blood cultures with PAF up regulated TLR2- induced TNF production. Addition of PAF did not alter TNF release induced by LPS. E. coli induced higher levels of TNF than S. aureus and the treatment with WEB2170 lead to a significant reduction of S. aureus-induced TNF release. However, addition of PAF did not significantly alter bacteria-induced TNF production. With E. coli neither treatment with WEB2170 nor with PAF modulated TNF release. Results indicate that PAF can increase or decrease TNF production induced by TLR2 depending on the time when PAF is combined with TLR2. The increase of the TNF production after extended priming with PAF it was not caused by an increase in TLR2 expression. Thus, it is suggested that interaction between PAFR and TLR2 signaling determines the levels of TNF release. TLR2/PAF/TNF signaling pathway can be relevant in innate immune responses against Gram positive bacteria as well as in inflammatory diseases.